The new normal challenges of managing business, social and ecological systems in the post covid-19 era - Chaturvedi, Harivansh [ed.]; Dey, Ajoy Kumar [ed.]; Singh, Nimisha [sub-ed.]; Mishra, Shreya [sub-ed.] (New Delhi Bloomsbury Publishing, 2021)
Each article in the book demystifies the multidimensional impact that the pandemic has had on the professional and personal spheres of the human lives. The authors who have shared their knowledge and research hail from Austria, Bangladesh, France, India, Indonesia, Malaysia and USA. Further, the fact that the authors include University Vice Chancellors, Directors, and Distinguished Professors, suggests that the insights provided in the articles are unparalleled, diverse, boundaryless and unique.The 23 articles in this book are divided in 5 sections namely Families Disconnecting or Reconnecting, Disrupted Lives During Pandemic, Reflecting on Professional Life, Revisiting Organizational Culture and Well-being, and Business and Academia Surviving the Crisis.
Keywords: COVID-19 (Disease) -- Social aspects; COVID-19 (Disease) -- Economic aspects